Adsorption of Zn(II) by Corncob Microwave Pretreated and Modified with Succinic Anhydride - Xu, Xingzhi; Yang, Xuejing; Yang, Yaling; Liu, Mousheng (Asian Journal of Chemistry, 2010)
A new adsorbent was prepared by modifying microwave pretreated corncob with succinic anhydride. The microwave pretreated corncob and un-pretreated corncob were both modified with succinic anhydride to get the products C 1 and C 2 from original corncob (C 0). Mass per cent gains (MPG) of both products were tested. The adsorptions of C 1, C 2 and C 0 with Zn2+ were studied. SEM, XPS and FTIR were utilized to investigate the structure and morphology of C 1. The results showed that C 1 had a fold phase covered with carboxyl groups which resulted in a high adsorption of metal ion. In the range of experiments, mass per cent gains of C 1 achieved 41.4 % in optimal microwave conditions, which exhibited an increase of 12.9 % from C 2 (28.5 %). After being treated with Zn2+ at room temperature, C 1 could reach a saturated adsorption capacity of 2.028 mmol/g, increased 1.747, 0.457 mmol/g in relation to C 0 (0.281 mmol/g) and C 1 (1.773 mmol/g), respectively. Its adsorption followed isotherm of Langmuir. The results indicated that the adsorption properties of C 1 were improved obviously. It can be used as a potential metal ion adsorbent.